Control del cabeceo, alabeo, orientación y altura en un helicóptero no tripulado (2014)
A Helicopter is a system that has great complexity in kinematic and dynamic analysis, the answer is not completely faithful to a specific model and involves many variables when analyzing its operation, therefore the correct interpretation and use of each a, requires precise instrumentation and proper processing of the signals obtained, at the same time the system is also sensitive to changes in the environmental and initials conditions, which makes it inevitable that each flight be unpredictable and different when the controllers of the actuators are not properly adjusted.